Guava powder production using pilot scale spray dryer and nutrient retention study - Kogulan, M. Saiger (2008)
For drying run, highly concentrated puree were prepared from guava. Maltodextrin 10 to the prepared puree as a carrier. The Pilot Scale Spray Dryer model ZLG-10 used for drying process. Retention of nutrients in food during processing is nowadays an important matter for food processors. This is mainly due to the change of food consumption pattern, the current market demand and the regulatory requirement. The study investigates some of the important aspects involved in spray drying processing of guava, a tropical fruit which among all the fruits ranked second in terms of vitamin C content and, also, has a high amount of fiber. In this study, water activity and temperature effect on nutrient retention of guava juice in spray drying process investigated. The best temperature to spray dry which gives low deterioration of vitamin C is identified too. Vitamin C is known as the least stable one among all the nutrients, thus it is selected as an index for nutrient retention study. HPLC analyses were performed to determine vitamin C level in spray dried and initial guava puree.The research shows 170oC is most fine and applicable temperature compare to any other temperature to give minimum vitamin C loss. Vitamin C deterioration depends both on temperature and water activity but experimentally proved water activity would play a more dominant role compared to temperature. Hence, a fast reduction of moisture content at higher temperature will help retaining vitamin C. First order reaction is used to describe the deterioration of vitamin C in spray drying process. Author